THE RELATIONSHIP BETWEEN EXCLUSIVE BREAST FEEDING WITH DDTK ASSESSMENT IN CHILDREN AGED 6 MONTHS TO 2 YEARS AT POSYANDU ANGGREK PETERONGAN, JOMBANG - Sri Banun Titi Istiqomah; Dewi Triloka Wulandari; Zakiya Salsabila; Rena Yanti (International Journal of Social Science, 2021)
Exclusive breastfeeding means breastfeeding without food and drink for babies aged 0-6 months. Data obtained from the 2010 IDHS stated that impaired growth and development of toddlers in Indonesia was caused by mothers who were disobedient in giving exclusive breastfeeding to their babies. The aim of the study was to analyze exclusive breastfeeding with a DDTK assessment in children aged 6 months to 2 years at the Orchid Posyandu, Peterongan District, Jombang Regency in 2020. The research design used is an analytical method with an approachcross sectional, the samples taken were some mothers who had toddlers aged 6 months to 2 years at the Orchid Posyandu, Peterongan District, Jombang Regency in 2020. Those who met the sample criteria byNonprobability Sampling, techniqueSimpel Random Sampling. The number of samples in this study were 48 respondents. The data obtained is tabulated and grouped to determine the relationship between the two variables. After that the data is entered into the testSPSS by analysisMann Whitney U with a significance level of p <0.05. the results of the study obtained a significance value of 0.001, so a p value <0.05, H was obtained1 accepted means that there is a relationship between exclusive breastfeeding and DDTK assessment in children aged 6 months to 2 years. Based on the results of this study, it is hoped that all health workers in the Peterongan District will further improve their performance through counseling activities and data collection on exclusive breastfeeding to achieve the desired toddler development.